Asymmetric [3+2] cycloaddition of 3-amino oxindole-based azomethine ylides with α, β-ynones: a straightforward approach to spirooxindoles incorporating 2, 5-dihydropyrroles and pyrroles. Issue 34 (12th April 2017) - Zhu, Guodong; Wu, Shiqi; Bao, Xiaoze; Cui, Longchen; Zhang, Yanpeng; Qu, Jingping; Chen, Hongbo; Wang, Baomin
Abstract : An organocatalytic asymmetric [3+2] cycloaddition to α, β-ynones is reported. Abstract : An organocatalytic asymmetric [3+2] cycloaddition of 3-amino oxindole-based azomethine ylides and α, β-ynones has been developed. This reaction afforded spiro[dihydropyrrole-2, 3′-oxindole] products in high chemical yields with excellent stereoselectivities (up to 99% yields, >20 : 1 dr and >99% ee). Notably, a series of important spiro[pyrrole-oxindole] derivatives were readily obtained via oxidation of the cycloadducts, thus extending the diversity of the products.